Comparison of clinical effectiveness between stapled transanal rectal resection and procedure for prolapse and hemorrhoids for young male patients with prolapsed hemorrhoids - Pei Yan; Gao Jihua; Qi Wenyue; Tian Maosheng; Wu Qiong; Duan Bingqian; Wang Ran; Liu Ziyi (结直肠肛门外科)
[Objectives] To compare the clinical effectiveness between stapled transanal rectal resection (STARR) and procedure for prolapse and hemorrhoids (PPH) for young male patients with prolapsed hemorrhoids. [Methods] This was a retrospective analysis of 84 young male patients with prolapsed hemorrhoids who were treated at the Department of Colorectal Surgery, The First Affiliated Hospital of Hebei College of Chinese Medicine, between January 2019 and December 2019. Depending on the surgical technique, patients were divided into the treatment group (receiving STARR, n=44) and the control group (receiving PPH, n=40). The followings were compared between the two groups: rate of symptom improvement, postoperative pain, anal function (Wexner anal incontinence score), postoperative complications (anal distension, anal edema, and anal stricture), and quality of life (measured using the SF-36). [Results] At 12 months after surgery, the rate of symptom improvement was significantly higher in the treatment group than in the control group (P<0.05). Pain score of visual analog scale (VAS) at 1 day after surgery did not differ significantly between the two groups (P>0.05); Pain score of VAS at 7 days after surgery was significantly lower in the treatment group than in the control group (P<0.05). Preoperative Wexner anal incontinence score did not differ significantly between the two groups (P>0.05); At 6 months after surgery, Wexner anal incontinence score decreased significantly in both groups and was significantly lower in the treatment group than in the control group (P<0.05). Incidences of anal distension, anal edema, and anal stricture within 3 months after surgery were significantly lower in the treatment group than in the control group (P<0.05). Preoperative SF-36 dimension scores did not differ significantly between the two groups (P>0.05). At 6 months after surgery, SF-36 dimension scores increased significantly in both groups and the treatment group had significantly higher dimension scores of physical function, role physical, vitality, and mental health (P<0.05). [Conclusion] For young males with prolapsed hemorrhoids, STARR has advantages over PPH in improving symptoms, quality of life, and anal function, as well as in reducing postoperative complications and postoperative pain.